The unusual presentation of sertoli-leydig cell tumor: a case report - Verma, Aruna; Bharti, Ritu; Sharma, Yamini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Sertoli cell tumor is very rare variety of ovarian Sertoli‐Leydig cell tumors. Due to nonspecific clinical and imaging features, diagnosis is often made after histopathological examination. Sertoli cell tumors usually presents with the features of virilization. The prognosis is excellent as most are detected in the early stages and surgical resection is often curative in most cases. Here we present a case of Sertoli Cell tumor, where no feature of virilization was present.